Productivity and profitability of rice varieties under different methods of establishment - Ghasal, P.C.; Bir, Dharam; Yadav, Ashok; Prakash, Ved; Verma, R.K. (Annals of Agricultural Research, 2016)
A field experiment was conducted to study the effect of establishment methods on productivity and profitability of different rice varieties during kharif 2011. The results revealed that growth parameters,number of effective tillers and chaffy grain-panicle were higher under direct seeded rice (DSR) method while panicle length, grains-panicle and test weight were higher under puddle transplanted rice (PTR) method. Grain yield (4.73 t ha-1) was recorded highest under PTR while B:C was the highest under DSR. Among the different varieties, 'HKR 48' recorded highest grain yield (5.06 tha-1) while the highest B:C (2.34) was under 'PB 1121' variety. Coarse grain varieties ('HKR 48', 'PR 114', 'HKR 47' and 'HKR 127') were found promising under PTR, while basmati varieties ('PB 1121' and 'CSR 30') performed equally under PTR and DSR.